Comparison of Macintosh, McCoy, and Glidescope video laryngoscope for intubation in morbidly obese patients: Randomized controlled trial - Keerthi P Nandakumar; Amar P Bhalla; Ravindra Kumar Pandey; Dalim Kumar Baidya; Rajeshwari Subramaniam; Lokesh Kashyap (Saudi Journal of Anaesthesia, 2018)
Objectives: The aim of the study was to compare time to intubation and glottic visualization between Macintosh, McCoy, and Glidescope video laryngoscope (GVL) in morbidly obese patients. Methodology: Forty-five American Society of Anesthesiologists I–III morbidly obese patients were randomized into three groups of 15 each and time to intubation, Cormack–Lehane grading, and Intubation Difficulty Score (IDS) were compared. Results: GVL took more time to intubate (TTI) compared to Macintosh and McCoy laryngoscope (P = 0.0001). Overall IDS were similar between the groups. Conclusion: To conclude, GVL takes longer TTI with no added advantage in IDS and hemodynamic response to intubation in morbidly obese patients. McCoy is only as effective as Macintosh and hence Macintosh laryngoscope should be laryngoscope of choice due to its widespread availability and familiarity.